IMPLEMENTASI TENTANG EFEKTIVITAS APARATUR PEMERINTAH TERHADAP PELAYANAN PUBLIK DI KECAMATAN BARONG TONGKOK KABUPATEN KUTAI BARAT - Nanik Pujiastuti Yonathan Tanna (ADMINISTRASI PUBLIK, 2017)
Yonathan Tanna (13.11.1001.3509.012). Implementation about Effectivenes Intrument Government to Public Service in Subdistrict Barong Tongkok Distric West Kutai. Program Study S1 Administration Public Science, science and Politic Faculty, University 17th August 1945 Samarinda. This research for to know Implementation about Effectivenes Intrument Government to Public Service in Subdistrict Barong Tongkok Distric West Kutai. This research is quantitative reserch. Technique removal sampel to the this research using technique simple random sampling. Instrument research using questionnaire and collecting data of filling quesioner. Experiment research intrument realized in Subdistrict Barong Tongkok Distric West Kutai. Validity experiment using correlation product moment from pearson. The research results showed that found relation positive and significant between apparatus effectiveness variable to public service in Subdistrict Barong Tongkok District West Kutai. This situation known result statistic test where coefficient correlation (r) is 0,975 this meaning available relationship very strong and positif being between both variable.